(3GdJShjb GdGNVQs - (3KGeQ(B, (3GdHcQjs; (3GdfhQj(B, (3GMeO fRGQs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2007)
(3eONd aj GdJShjb hGdJShjb GdCNVQ (B-(3GdHjFI GdWHjYjI hGdJShjb GdCNVQ (B-(3GdeRjL GdJShjbj GdCNVQ (B-(3GdeSJgdc GdCNVQ (B-(3JLRFI Shb GdeSJgdc GdCNVQ (B-(3GdTQGA GdCNVQ defXeGJ GdCYeGd (B-(3GdefJL GdCNVQ (B-(3GdJSYjQ Ydi hab eONd GdJShjb GdCNVQ (B-(3JQhjL GdefJLGJ GdNVQGA (B-(3JhRjY GdefJLGJ GdNVQGA (B-(3MGdGJ OQGSjI aj GdJShjb GdCNVQs
Keywords: (3GdHGYI haf GdHjYs; (3GdJShjbs; (3GdJShjb(B--(3adSaIs